Особливості підвищення енергетичної ефективності електромеханічної системи конвейєра - Печеник, Микола Валентинович; Бур'ян, Сергій Олександрович; Горбатовський, Андрій Олексійович (НТУ "ХПІ", 2013)
The issues of the energy efficiency modes of belt conveyor are considered. Defined levels and ranges of the controlled variable, which provides the highest power efficiency of electromechanical systems. The mathematical modelling of the control system was provided.
Features of improving energy efficiency of the conveyer electromechanical system
Keywords: енергозбереження; стрічкові конвеєри; енергетична ефективність конвеєра; коефіцієнт корисної дії; оптимальний регулятор; закон регулювання напруги